ANALISIS PENGARUH PENDAPATAN ASLI DAERAH TERHADAP PRODUK DOMESTIK BRUTO SETELAH SATU DEKADE OTONOMI DAERAH - Nasir, Muhammad Safar (Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose of study is to analyze the relationship and influence revenue (PAD) to the Gross Regional Domestic Product (GRDP). This study sampled in 2010 until 2013 the 10 areas that have the highest economic growth rate and the 10 areas that have the lowest economic growth rate. The method used is correlation and regression test panel data random effects (random effect of panel regression). Data sourced from documents retrieved and Government Finance Statistics District / City in 2009 - 2013. From the research, there is evidence that there is a positive relationship between the PAD and the GDP. Local Revenue (PAD) in the region with the highest economic growth rate has a significant effect on the GDP. However, these results inversely in the region with the lowest economic growth rate which the PAD no significant effect on the GDP.Keyword: PAD, PDRB